Literature Review of Burnout Syndrome in Intensive Care Unit (ICU) Staffs During The COVID-19 Pandemic - Lazuwardi, Rasya Azka; Aziz, Afifur Rafi Hilmi; Qamar; Nadira Putri Nastiti; Papageorgiou, Platon (Jurnal Psikiatri Surabaya, 2023)
Introductions: Burnout syndrome becomes a special concern for health workers during COVID-19 pandemic that has been exposed to increased workload and intense working hours with COVID-19 patients, stating having a high risk of getting infected with COVID-19 as well. Methods: This literature review paper reviewed scientific journals with prevalence and burnout syndrome profile data. The journals were obtained through the search engines GoogleScholar, the MEDLINE (PubMed) database and PsychINFO. From the search, there are 13 articles in total that meet the required data criteria. Results: Prevalence of burnout syndrome were found severely high in ICU settings, it reached more than 50% from most of the survey. Burnout syndrome rate can be influenced by working conditions, age and gender, time of work and working experience. Burnout syndrome can manifest as higher fatigue level and decrease of cognitive function that can increase the risk of medical mistake. Conclusions: High prevalence and severity of burnout syndrome oblige us to pay attention to symptoms that can affect professional intensive care unit staff and its service to patients. Further research should review prevention therapy and how to apply to health workers and also the prevalence of prevention that has been done in other studies.